2015
DOI: 10.1021/ac504587h
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Sensor for Pattern Recognition of Proteins Based on DNA–Gold Nanoparticles Conjugates

Abstract: We presented an extensible multidimensional sensor with conjugated nonspecific dye-labeled DNA sequences absorbed onto gold nanoparticles (DNA-AuNPs) as receptors. At the presence of target protein, DNA was removed from the surface of AuNPs due to the competitive binding, which resulted in a red-to-blue color change along with salt-induced aggregation of AuNPs for colorimetric analysis and fluorescent "turn-on" signal of the labeled dye for fluorescence analysis. The orthogonal and complementary fluorescent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…It is known that the very complex matrixes in human urine is highly challenging for the identification of proteins and other biological targets. 25 However, in the present case, each of the relevant proteins involved in the urine sample matrix generated a distinct response, and a 100% identification accuracy is achieved for all the 6 proteins. This observation indicated that the sensing array system based on QDs/IL-QDs conjugates offers promising potential for the discrimination of proteins in real biological samples.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…It is known that the very complex matrixes in human urine is highly challenging for the identification of proteins and other biological targets. 25 However, in the present case, each of the relevant proteins involved in the urine sample matrix generated a distinct response, and a 100% identification accuracy is achieved for all the 6 proteins. This observation indicated that the sensing array system based on QDs/IL-QDs conjugates offers promising potential for the discrimination of proteins in real biological samples.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…The sensing system showed various color changes due to different properties of every protein, such as pI, molecular weight. The variation of the color change as fingerprint could be used to discriminate proteins (Sun et al, 2015;Lu et al, 2013aLu et al, , 2013b. The absorption profiles see Fig.…”
Section: Principle Of Colorimetric Methods For Protein Detectionmentioning
confidence: 99%
“…In the past few years, many kinds of materials, such as organic compounds (Jiménez et al, 2004;Schmittel and Lin, 2007), inorganic compound films (Hu et al, 2011), nanoparticles (Li et al, 2014;Liu et al, 2010;Lu et al, 2013aLu et al, , 2013bRana et al, 2015;Wang et al, 2009), graphene oxide (Lu et al, 2013a(Lu et al, , 2013b and quantum dots (Sang and Wang, 2014;Wu et al, 2011) have been reported as the single transducer with fundamentally different transduction principles for detection of various analytes. Recently, we have proposed an extensible multidimensional sensor array based on DNA-AuNPs conjugates with dual-channel (fluorescence and colorimetric), which could easily increase the number of sensing elements by simply changing the DNA sequences for enhancing discrimination ability of the sensor (Sun et al, 2015). However, in all the previous works, a variety of measure techniques were used to record many signal responses for target analytes against the multidimensional sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, fluorophore-conjugated ssDNAs are capable of generating differential optical signals following interactions with different proteins. There are a number of sensing systems that employ complexes of ssDNAs and other materials, such as gold nanoparticles [ 29 , 30 , 31 ], metal oxide nanoparticles [ 32 , 33 ], graphene oxide nanosheets [ 34 , 35 , 36 , 37 , 38 ], and metal oxide nanosheets [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%